Implementation of an Optical-Wireless Network with Spectrum Sensing and Dynamic Resource Allocation Using Optically Controlled Reconfigurable Antennas - E. Raimundo-Neto; J. R. G. da Rosa; M. A. F. Casaroli; I. Feliciano da Costa; A. M. Alberti; Arismar Cerqueira Sodré (International Journal of Antennas and Propagation)
This work proposes the concept and reports the implementation of an adaptive and cognitive radio over fiber architecture. It is aimed at dealing with the new demands for convergent networks by means of simultaneously providing the functionalities of multiband radiofrequency spectrum sensing, dynamic resource allocation, and centralized processing capability, as well as the use of optically controlled reconfigurable antennas and radio over fiber technology. The performance of this novel and innovative architecture has been evaluated in a geographically distributed optical-wireless network under real conditions and for different fiber lengths. Experimental results demonstrate reach extension of more than 40 times and an enhancement of more than 30 dB in the carrier to interference plus noise ratio parameter.